Mexico : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper assesses the economic impact of Mexico's structural reforms. The Mexican authorities have been implementing an ambitious structural reform agenda in a coordinated effort to lift productivity growth. The reforms have targeted a broad range of industries; dissolved state monopolies; and addressed labor market, education, and governance shortcomings. The analysis suggests that external headwinds have masked evidence that the reforms are achieving many of the intended transformations in the targeted sectors. Priority should go to reforms targeting the rule of law and attendant improvements in security and reduction of corruption. These will not only improve the business environment but are key to the success of existing reform efforts.